To the question of Rank effect essence - V. I. Kuznetsov; V. V. Makarov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The work considers a vortex tube. There is examined the impact of stratification and periphery of axial gas layers at full temperature due to exchange work and warmth between them. There is developed mechanism for the transfer of kinetic energy from the axis towards the periphery. There are retrieved forces influence the viscosity gradient angular velocities on energy exchange in the Vortex tube. Experimentally there is found dependence of energy transfer from the thermophysical properties of gas pressure gas inlet swirl tube and exit valve and diaphragm from the weight percentage of cold flow, main elements of geometric parameters of vortex pipes. Work is carried out to identify the dependencies of thermal efficiency of the length of the Vortex tube. There is conducted research to identify the entity Vortex effect-stratification layers of gas temperature